2021
DOI: 10.3389/fphar.2021.596287
|View full text |Cite
|
Sign up to set email alerts
|

Multipronged Attack of Stem Cell Therapy in Treating the Neurological and Neuropsychiatric Symptoms of Epilepsy

Abstract: Epilepsy stands as a life-threatening disease that is characterized by unprovoked seizures. However, an important characteristic of epilepsy that needs to be examined is the neuropsychiatric aspect. Epileptic patients endure aggression, depression, and other psychiatric illnesses. Therapies for epilepsy can be divided into two categories: antiepileptic medications and surgical resection. Antiepileptic drugs are used to attenuate heightened neuronal firing and to lessen seizure frequency. Alternatively, surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 150 publications
(178 reference statements)
0
3
0
Order By: Relevance
“…The utility of in vitro stem cell technology by patient-derived iPSCs to high-throughput screening of anti-seizure medications can be applied for personalized epilepsy therapy (Jiao et al, 2013 ; Kaufmann et al, 2015 ; Elitt et al, 2018 ; Lybrand et al, 2020 ). The potential major roles of stem cell therapy in epilepsy are seizure remission, inhibition of the progression of the epileptogenic process, prophylaxis against the development of chronic epilepsy, and improvement of cognitive function (Aligholi et al, 2021 ; Sadanandan et al, 2021 ; Ramos-Fresnedo et al, 2022 ). A phase I clinical trial study showed a favorable seizure reduction, a good safety profile, and improvement of pathological hallmarks in epilepsy patients treated with autologous MSCs (Hlebokazov et al, 2017 ).…”
Section: Therapeutic Applications and Effects Of Stem Cells In Epilepsymentioning
confidence: 99%
“…The utility of in vitro stem cell technology by patient-derived iPSCs to high-throughput screening of anti-seizure medications can be applied for personalized epilepsy therapy (Jiao et al, 2013 ; Kaufmann et al, 2015 ; Elitt et al, 2018 ; Lybrand et al, 2020 ). The potential major roles of stem cell therapy in epilepsy are seizure remission, inhibition of the progression of the epileptogenic process, prophylaxis against the development of chronic epilepsy, and improvement of cognitive function (Aligholi et al, 2021 ; Sadanandan et al, 2021 ; Ramos-Fresnedo et al, 2022 ). A phase I clinical trial study showed a favorable seizure reduction, a good safety profile, and improvement of pathological hallmarks in epilepsy patients treated with autologous MSCs (Hlebokazov et al, 2017 ).…”
Section: Therapeutic Applications and Effects Of Stem Cells In Epilepsymentioning
confidence: 99%
“…In the last decade, different approaches have attempted to prevent seizures and to control them. These treatments, some obtained from pre-clinical studies, ranging from pharmacological therapies based on new compounds such as resveratrol or vitamin E [22,23]; cell therapies rooted on stem cells, interneuron precursor transplants [24][25][26] or reprograming reactive glia into interneurons [27], and gene therapies such as neuropeptide Y transfection [28,29] to clinical studies in humans, such as modern surgery with laser-induced thermal therapy (LITT); magnetic resonance-guided LITT (MRgLITT) [30,31]; brain stimulation [32,33], or even controlling seizures with diet such as a ketogenic diet or other regimens [34]. Since most AEDs available in the market are only preventing and treating the symptoms instead of acting on the molecular mechanisms, they produce numerous negative side effects that limit their therapeutic use [35][36][37].…”
Section: Etiology and Treatmentmentioning
confidence: 99%
“…Stem cells are defined as a group of cells with unlimited proliferation, self-renewing, and multilineage differentiation potential. , Novel therapies using stem cells have been evidenced with premium therapeutic efficacy in the treatment of diverse devastating diseases such as epilepsy, neonatal hypoxic-ischemic encephalopathy, autoimmune disease, and diabetic kidney disease. However, one of the critical issues is the poor survival rate and potential tumorigenesis of stem cells after implantation in vivo . ,, Compared with pluripotent stem cells, such as induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs), mesenchymal stem/stromal cells (MSCs) lack tumorigenicity, have lower immunogenicity, and will not raise ethical concerns . Recent studies showed that paracrine effects of stem cells might predominate over cell differentiation during tissue repair. , The paracrine effects include anti-inflammation, antiapoptosis, host cell recruitment, enhanced cell proliferation, and proangiogenesis. Compared to living cells, the secreted bioactive molecules, namely stem cell secretome, have various advantages such as easy preparation and storage, which are essential for their clinical applications. …”
Section: Introductionmentioning
confidence: 99%